“Bolot’ana Lucroza” by V. Petrov-Domontovych: peculiarities of metatext - Зубань, Віра Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The purpose of this research is to present peculiarities of critical discourse V. Domontovych’s “Bolot’ana Lucroza” (1947–1948) in vertical context publishing on 1947 “Memoirs about neoclassics” by Y. Klen (O. Burghardt) on stage statement of individual-author’s conception Ukrainian neoclassicism on 1920s: from sources and premises appearance new phenomenon of modernism, its cognition-ethical meaning for Ukrainian reality to produce subjective experienced and author’s self-affirmative as neoclassic.